Proceedings of the 2019 Conference of the North 2019
DOI: 10.18653/v1/n19-1253
|View full text |Cite
|
Sign up to set email alerts
|

On Difficulties of Cross-Lingual Transfer with Order Differences: A Case Study on Dependency Parsing

Abstract: Different languages might have different word orders. In this paper, we investigate crosslingual transfer and posit that an orderagnostic model will perform better when transferring to distant foreign languages. To test our hypothesis, we train dependency parsers on an English corpus and evaluate their transfer performance on 30 other languages. Specifically, we compare encoders and decoders based on Recurrent Neural Networks (RNNs) and modified self-attentive architectures. The former relies on sequential inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 43 publications
0
89
1
Order By: Relevance
“…At evaluation time, we follow the same approach as training time except for parsing. We threshold the sentence length to 140 words, including words and punctuation, following Ahmad et al (2019). In practice, the maximum subwords sequence length is the number of subwords of the first 140 words or 512, whichever is smaller.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At evaluation time, we follow the same approach as training time except for parsing. We threshold the sentence length to 140 words, including words and punctuation, following Ahmad et al (2019). In practice, the maximum subwords sequence length is the number of subwords of the first 140 words or 512, whichever is smaller.…”
Section: Methodsmentioning
confidence: 99%
“…Before the widespread use of cross-lingual word embeddings, task-specific models assumed coarse-grain representation like part-of-speech tags, in support of a delexicalized parser (Zeman and Resnik, 2008). More recently cross-lingual word embeddings have been used in conjunction with task-specific neural architectures for tasks like named entity recognition (Xie et al, 2018), part-of-speech tagging (Kim et al, 2017) and dependency parsing (Ahmad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Both directions do not directly address structure. Ahmad et al (2019) showed structuralsensitivity is important for modern parsers; insensitive parsers suffer. Data transfer is an alternative solution to alleviate the typological divergences, such as annotation projection (Tiedemann, 2014) and source treebank reordering (Rasooli and Collins, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…Many experiments (Ahmad et al, 2019) suggest that to achieve reasonable performance in the zeroshot setup, the source and the target languages need to share similar grammatical structure or lie in the same language family. In addition, since mBERT is not trained with explicit language signal, mBERT's multilingual representations are less effective for languages with little lexical overlap (Patra et al, 2019).…”
Section: Introductionmentioning
confidence: 99%